2005
DOI: 10.1007/s00425-005-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression of a metallothionein gene in the aquatic fern Azolla filiculoides under heavy metal stress

Abstract: A cDNA encoding a type 2 metallothionein (MT) was isolated from Azolla filiculoides, termed AzMT2, accession no. AF482470. The AzMT2 transcript was expressed in sterile A. filiculoides that were free of the cyanobiont Anabaena azollae after erythromycin treatment, proving that AzMT2 is encoded by the fern genome. AzMT2 RNA expression was enhanced by the addition of Cd(+2), Cu(+2), Zn(+2) and Ni(+2) to the growth medium. The transcript level of AzMT2 correlated with the metal content in the plants. Temporal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…It was reported that the transcript levels of type 2 MT from bean were not remarkably affected by treatment with Cu, Zn or Cd (Foley and Singh, 1994). In aquatic fern Azolla filiculoides, however, the type 2 MT gene AzMT2 expression was increased by Cd, Cu, Zn and Ni treatments (Schor-Fumbarov et al 2005). In rice, the expression of ricMT in seedling shoots was elevated by the addition of metal ions, such as Cu, Zn, Cd, Fe, Pb and A1, while in roots it was reduced in the presence of these metal ions except copper (Yu et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…It was reported that the transcript levels of type 2 MT from bean were not remarkably affected by treatment with Cu, Zn or Cd (Foley and Singh, 1994). In aquatic fern Azolla filiculoides, however, the type 2 MT gene AzMT2 expression was increased by Cd, Cu, Zn and Ni treatments (Schor-Fumbarov et al 2005). In rice, the expression of ricMT in seedling shoots was elevated by the addition of metal ions, such as Cu, Zn, Cd, Fe, Pb and A1, while in roots it was reduced in the presence of these metal ions except copper (Yu et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…The metallothioneins are small proteins rich in cysteine residues, and they work as cell metal chelators efficient in metal detoxification (Schor-Fumbarov et al 2005). The metallothioneins are classified in four groups according to the distribution of the cysteine residues in their domains.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one report by Schor-Fumbarov et al (2005) who characterized metallothioneins from Azolla filiculoides (Accession No. AF482470) grown under heavy metal stress.…”
Section: Molecular Mechanism Of Metal Hyperaccumulationmentioning
confidence: 99%
“…Type 3 includes many MTs identified as being expressed during fruit ripening, and type 4 MTs, exemplified by the wheat Ec protein are expressed only in seeds (Cobbet and Goldsbrough 2002). Schor-Fumbarov et al (2005) concluded that metalloprotein, AzMT2 in Azolla filiculoides showed significant similarity to type 2 MTs in plants and is encoded by the fern genome. The temporal analysis of AzMT2 indicates participation of this MT in both the homeostasis of essential metals as well as detoxification of toxic metals.…”
Section: Molecular Mechanism Of Metal Hyperaccumulationmentioning
confidence: 99%